Analysis of composite variance of experiments carried out according to design Latin box - خلف, كمال علوان; عبد الحسين, كاظم يحيى (Journal of Economics and Administrative Sciences, 2012)
We know that the experiments which conducted by latin square in one location or in one period (season), but there are many cases that need to conduct the same experiments in many locations or in many periods (seasons) to study the interaction  between the treatments and locations or between the treatments and periods (seasons) .In this research we present  an idea for  conduct  the experiment in several locations and in many period (seasons) by using LSD , it represent  acontribution in the area of design and analysis of experiments ,we had written. we had written (theoretically)  the general plans, the mathematical models for these experiments, and finding the derivations of EMS for each component (source) of sources of variation of the analysis of variance tables which uses for the statistical analysis for these experiments.